2011
DOI: 10.1161/atvbaha.111.223669
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Pro-Brain Natriuretic Peptide and Risk of Cardiovascular Events in a Japanese Community

Abstract: Objective-Few studies have examined the association between natriuretic peptides and the incidence of cardiovascular disease (CVD) in Asian populations. Methods and Results-A total of 3104 community-dwelling Japanese individuals aged Ն40 years without history of CVD were followed up for 5 years. A total of 127 CVD events were identified. The age-and sex-adjusted incidence of CVD increased with increasing N-terminal pro-brain natriuretic peptide (NT-proBNP) levels (Ͻ55, 55-124, 125-399, and Ն400 pg/mL) at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…Two cut-off points each were used to define elevations of the serum TnT level (!0.014 ng/mL and !0.010 ng/mL) [4,5,16,19] and elevation of the serum NTproBNP level (!125 pg/mL and !55 pg/mL) [17,20]. Diabetes mellitus was defined as a history of receiving medication for diabetes mellitus and/or glycated hemoglobin A1C !6.5%.…”
Section: Laboratory Measurements and Definitionsmentioning
confidence: 99%
“…Two cut-off points each were used to define elevations of the serum TnT level (!0.014 ng/mL and !0.010 ng/mL) [4,5,16,19] and elevation of the serum NTproBNP level (!125 pg/mL and !55 pg/mL) [17,20]. Diabetes mellitus was defined as a history of receiving medication for diabetes mellitus and/or glycated hemoglobin A1C !6.5%.…”
Section: Laboratory Measurements and Definitionsmentioning
confidence: 99%
“…The Hisayama study followed up Japanese residents for 5 years, and found an elevated stroke risk in those with NT-proBNP ≥125.0 pg/mL. 9 The predictive value of NT-proBNP beyond 5 years, however, remains an unsettled issue in an Asian patients.…”
Section: Discussionmentioning
confidence: 99%
“…9,30 The C-statistic for cardiovascular disease prediction increased by 0.021 in the Hisayama study and by 0.016 in the German study after adding NT-proBNP to the base model. 9,30…”
Section: Advance Publication By-j-stagementioning
confidence: 99%
See 1 more Smart Citation
“…We first assessed associations between the characteristics of the participants and NT-proBNP at least 125 pg/ml, which indicates heart failure [11,20,21]. We then compared means and proportions using Student's t-test, and the chi-squared or Fisher's exact tests.…”
Section: Discussionmentioning
confidence: 99%